Chromosome-level genome assembly of the yellow boxfish (Ostracion cubicus) provides insights into the evolution of bone plates and ostracitoxin secretion - Wei, Shichao; Zhou, Wenliang; Fan, Huizhong; Zhang, Zhiwei; Guo, Weijian; Peng, Zhaojie; Wei, Fuwen (Frontiers in Marine Science, 2023)
The Ostracion cubicus, commonly known as the yellow boxfish, is a remarkable species with a body encased in a bone plate and the ability to produce an ostracitoxin from their skin when under stress. However, the genetic basis of those effective defense traits is still largely unknown due to the lack of genomic resources. Here, we assembled the first chromosome-level genome of O. cubicus with 867.50 Mb in genome size and 34.86 Mb N50 scaffold length by HiFi and Hi-C sequencing. Twenty-five pseudo-chromosomes, numbered according to size, covered 94.13% of the total assembled sequences. A total of 23,224 protein-coding genes were predicted, with a BUSCO completeness of 98.6%. Positive selection or rapid evolution was observed in genes related to scale and bone development (acsl4a, casr, keap1a, tbx1), and up-regulation of transcription was found in the skin of boxfish (bmp1, bmp2k, bmp4, bmp7, smad5, suco, prelp, mitf), likely associated with the bone plates evolution in the yellow boxfish. An expansion of the solute carrier family 22, a cluster of genes in solute carrier (SLCs) family, transmembrane protein family (TMEMs), vesicle trafficking (SECs), ATP-binding cassette (ABCs) and apolipoproteins (APOs) were identified under positive selection, rapid evolution, or up-regulated in the skin of boxfish, likely associated with the ostracitoxin secretion in the yellow boxfish. Our study not only presents a high-quality boxfish genome but also provides insights into bone plates evolution and ostracitoxin secretion of O. cubicus.